PENINGKATAN PENGETAHUAN REMAJA PUTRI TENTANG KEBERSIHAN ALAT KELAMIN PADA SAAT MENSTRUASI MELALUI PENYULUHAN DI KELURAHAN WONOLOPO KECAMATAN MIJEN - Irmayanti, Ayu Dewi; Wardani, Ratih Sari; Indrawati, Nuke Devi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Woman who had a period has to keep hygiene  their sex organ because at menstruation times their uterus veins were opened and could be easily infected. Pre study result showed that 6 of 10 adolescent girl in Wonolopo village don’t know  sex organ hygiene at menstruation times. Therefore it is important to conduct some health education about sex organ hygiene at menstruations times. To know the enhancement of adolescent girl knowledge about sex organ cleanness at menstruation times by passing counseling in Wonolopo village Mijen District. This research is quasy experiment research with Pre Test Post Test Design.  The population of this research is adolescent girl RW IV Wonolopo village amount to 57 people. Samples were taken to amount to 36 people. The sampling technique being applied was simple random sampling. Independent variable is counseling sex organ cleanness at menstruation times. Dependent variable is knowledge about sex organ cleanness at menstruation times. Statistic test was applied by using Wilcoxon test. Knowledge before helath education has mean score 10,89 and knowledge after health education  increases to be 18,31. Based on Wilcoxon test estimation p-value 0,000 (<0,05) so that there is a significant difference of knowledge about sex organhygienes at menstruation times between before and after health education. There is a significant knowledge difference between before and after health education. Key Word: Knowledge, Sex Organ Cleanness At Menstruation Times, Adolescent Girl